Literature Review: Analysis of Exposure of Vehicle Emission Gases (Co, No2, So2, Pm2.5, and Pm10) to Public Health Risks - Jhon Wesly Sitanggang; Elvi Sunarsih; Hamzah Hasyim (International Journal Labs, 2023)
Exhaust emissions are pollutants that pollute the air created by vehicle exhaust gases. Vehicle exhaust gas is defined as the residual gas of the combustion process which is released into the free air through the vehicle exhaust duct. People can be at risk of air pollution from various pollutants, namely people who use roads, people who live on the roadside, and people who work on highways such as traffic police, street vendors, hawkers, and street children who busk at crossroads. The purpose of this study is to discuss and analyze the stages and procedures in the process of conducting an environmental health risk analysis of pollutant pollution in the air. This writing uses the Literature Review method and selection criteria for including carried out from 2018-2023. Calculation of the amount of health risk using the Environmental Health Risk Analysis (ARKL) method. Based on the literature review of these articles, there are still several risk agents (CO, NO2, SO2, PM2.5, and PM10) sources of air pollution that have values above the specified quality standards (RQ1). This is a risk to health both carcinogenic and non-carcinogenic. The impact can occur respiratory disorders and other body systems both in realtime and lifetime. Based on the calculation of the RQ?1 value, exposure to air pollutants in the community will be continued at the risk control and risk communication stages.